On Ternary Monoid of All Hypersubstitutions of Type \(τ=(2)\) - Chansuriya, Nagornchat; Leeratanavalee, Sorasak (Communications in Mathematics and Applications, 2019)
The present paper gives the concept of a ternary monoid \(Hyp(2)\) and studies some algebraic-structural properties of this monoid. We consider some submonoids of \(Hyp(2)\) and study the relationship between these submonoids.
Keywords: Hypersubstitutions; Ternary semigroup; Ternary ideal